Semangat and atomic energy : Malay folklore and the demise of colonialism in Malaya - Gan, Zhen Hui (Nanyang Technological University, 2021)
In this paper, I will discuss the contributions of Othman Wok and J.N. McHugh to the literature on Malay folklore in colonial Malaya, in the form of their respective publications, Malayan Horror and Hantu Hantu. Through my analysis of their approaches to Malay folklore, I will argue that these publications reflect the contrasting attitudes of the Malays and the British towards the demise of colonialism in Malaya. The stories in Malayan Horror integrated modernity into Malay folklore, reflecting the era’s spirit of innovation as well as an optimism for Malaya’s future. Meanwhile, Hantu Hantu sought to preserve Malay folklore in what was believed to be its most authentic form, revealing a nostalgia for the glory days of colonialism.